Scaffolding in reflective journaling: A means to develop higher order thinking skills in undergraduate learners - Mary-Ann Jarvis; Olivia B. Baloyi (Elsevier, 2020)
Background: Reflection through reflective journaling has the potential to assist learners to enhance their understanding, enrich lifelong learning, reduce clinical errors and develop professional autonomy grounded in expert clinical judgement. Aim: The study presents an analysis of scaffolding in reflective journaling as a means to develop higher order thinking skills (HOTS) in Bachelor Nursing fourth year students, psychiatric component. Methods and analysis: The study adopted a qualitative exploratory approach, underpinned by social constructivism. Non-probability purposive sampling was used. Data collection methods included two focus group discussions and document analysis. Content analysis using Elo and Kyngäs (2008) approach was followed for both sources of data. Data evaluation was done using Lincoln and Guba's methods of trustworthiness. Results: The following categories emerged: conscious incompetence, intervening conditions and simultaneous unintended outcomes. Conclusion: A phased introduction of reflective journaling (linked entries) supported by scaffolding is a strategy that can move the learner from the Zone of Proximal Development to that of an independent critical thinker able to use HOTS as an autonomous professional.